Pseudomonas mendocina bacteraemia secondary to cellulitis – a report and brief series of cases - Jorge Reis; Francisca Carmo; Inês Soares; Catarina Salvado; Mariana Fidalgo (European Journal of Case Reports in Internal Medicine)
Background: Pseudomonas mendocina is a rare cause of disease in humans with few cases described, but known to cause severe infections, mainly endocarditis and bacteraemia. Case description: An 86-year-old Caucasian male, with several vascular risk factors (type 2 diabetes, hypertension, dyslipidaemia, coronary heart disease and heart failure), who presented long-standing lower limb phlyctens for which he was being treated, developed lower limb cellulitis. When observed in the Emergency Department, he was septic and was admitted for treatment and surveillance. Blood cultures were positive for P. mendocina. He was treated with antibiotics and recovered, and was discharged home. Conclusion: Damage to the skin barrier as in cellulitis provides a point of entry for P. mendocina, a microorganism that lives in soil and water. The source of contamination is rarely identified, but immunocompromised people present a higher risk of infection and severe disease. The antibiotic susceptibility profile is different from the more common Pseudomonas aeruginosa, with fewer known resistances. Albeit rare, this is thought to be an underreported infection that clinicians should be aware of.